Kinship ties and entrepreneurship in Western Africa - (:unkn) unknown (My University, 2013)
Small entrepreneurs in poor countries achieve relatively high marginal returns to capital but show only low re-investment rates. The literature is rather inconclusive about the possible causes. We explore whether ‘forced redistribution’, i.e. abusive demands by the kin, affects the allocation of capital and labor to the household firm. We use an original data-set covering household firms in seven economic centers in Western Africa. We find some evidence that family and kinship ties within the city rather enhance labor effort and the use of capital. However, the stronger the ties to the village of origin the lower input use which is supporting the ‘forced redistribution’ hypothesis. Given that such redistribution is partly the consequence of a lack of formal insurance mechanisms, these results suggest that the provision of health insurance and other insurance devices may have positive indirect effects on private sector development.
Keywords: African Research